Identifying Learning Facilities at Kb Anyelir as a Learning Resource Environment - Pamungkas, Devan Putra Hedi; Mariana, Mariana; Hermita, Nur Cahya; Anggraini, Felisha Azzahra; Hikmah, Siti Nur; Azizah, Sagita Nurul; Sjamsir, Hasbi; Rozie, Fachrul (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
This study aims to identify and analyze the learning facilities at KB Anyelir in Samarinda as an effective learning resource environment that supports holistic early childhood development. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews, and documentation involving the principal, teachers, and parents as key informants. The findings reveal that KB Anyelir possesses well-organized and age-appropriate indoor and outdoor facilities designed to create a safe, engaging, and stimulating environment. Indoor facilities include bright, well-ventilated classrooms equipped with educational play tools such as blocks, puzzles, drawing materials, and thematic learning media. Outdoor areas consist of playgrounds, gardens, and natural exploration spaces that promote physical, social, and emotional development. The institution also emphasizes cleanliness, health, and the integration of environmental learning through activities like gardening, observing nature, and recycling projects. Parental and community involvement, alongside teachers’ creative use of learning environments, plays a crucial role in maintaining and optimizing facilities. The study concludes that the success of KB Anyelir in creating a conducive learning environment is determined not only by physical facilities but also by social participation, effective management, and the teachers’ ability to design meaningful, child- centered learning experiences. Continuous maintenance and collaborative engagement among all stakeholders are essential to sustain an inclusive, safe, and inspiring educational environment for early childhood development.